PENGARUH STRES KERJA DAN DUKUNGAN MANAJEMEN TERHADAP KEPUASAN KERJA (STUDI PADA BAGIAN PRODUKSI PT. DUTA PALMA NUSANTARA PEKANBARU) - Cindy Fitri Anisa; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to investigate and analyze the stress of work, management support and job satisfaction of employees in the production of PT. Duta Palma Nusantara Pekanbaru as well as to determine the effect of work stress and management support on employee job satisfaction in the production of PT. Duta Palma Nusantara Pekanbaru. Production employees at PT. Duta Palma Nusantara Pekanbaru have high levels of job stress high enough. Management support to the production employees at PT. Duta Palma Nusantara Pekanbaru rated still many shortcomings. This causes a lack of job satisfaction of employees in the production of PT. Duta Palma Nusantara Pekanbaru. The results of the analysis with SPSS, showed that the relationship between Work Stress (X1) and Management Support (X2) with Employee Satisfaction Part Production (Y) have a very strong relationship level. In addition work stress variable (X1) more dominant production employee job satisfaction (Y) at PT. Duta Palma Nusantara Pekanbaru compared with management support variable (Y).Keyword : job stress, management support, job satisfaction.